Discovery of 4,5,6,7-Tetrahydrothieno [3,2-b] Pyridine as Novel Fungicide Lead Scaffold - Ke Chen; Difan Deng; Yupeng Yin; Dongmei Xi; Phumbum Park; Wei Gao; Rui Liu; Kang Lei (Microorganisms)
To identify fungicide lead compounds with novel scaffold and high efficacy, a library of 4,5-dihydrotetrazolo [1,5-a]thieno [2,3-e]pyridine derivatives, consisting of 10 newly synthesized compounds and 12 previously reported compounds, was evaluated for their potential as fungicide agents. In vitro bioassay results indicated that some target compounds exhibited certain antifungal activity against the tested fungi at a concentration of 50 μg/mL. Especially, compounds I-1, I-5, I-7, and I-12 demonstrated promising antifungal activity against C. arachidicola, R. solani, and S. sclerotiorum, with EC50 values ranging from 4.61 to 6.66 μg/mL. Additionally, transcriptome analysis revealed that the molecular mode of action of compound I-12 involves the inhibition of nitrogen metabolism and the proteasome pathway. The present work demonstrates that 4,5,6,7-tetrahydrothieno [3,2-b] pyridine represents a promising lead scaffold and provides important theoretical foundations and innovative perspectives for the development of novel and highly efficient fungicides.